2018
DOI: 10.1016/j.molcel.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Active N6-Methyladenine Demethylation by DMAD Regulates Gene Expression by Coordinating with Polycomb Protein in Neurons

Abstract: A ten-eleven translocation (TET) ortholog exists as a DNA N-methyladenine (6mA) demethylase (DMAD) in Drosophila. However, the molecular roles of 6mA and DMAD remain unexplored. Through genome-wide 6mA and transcriptome profiling in Drosophila brains and neuronal cells, we found that 6mA may epigenetically regulate a group of genes involved in neurodevelopment and neuronal functions. Mechanistically, DMAD interacts with the Trithorax-related complex protein Wds to maintain active transcription by dynamically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 42 publications
(63 reference statements)
8
68
2
Order By: Relevance
“…Methylation of adenine, i.e., 6-mA, in GATC context has been reported for the survival of several bacteria, as DNA adenine methyl transferase (DAMT, the writer) creates specific methylation marks (Figure 3) that are important for DNA replication, mismatch repair, segregation, and regulation of gene expression (Ratel et al, 2006). 6-mA is known to play an important regulatory role in RNAs, and recent studies suggest the presence of 6-mA in eukaryotic genomes (Kigar et al, 2017; Yao et al, 2017, 2018). Moreover, oxidation of the methyl group of 6-mA by AlkB family of dioxygenases (e.g., 6-mA demethylases) results in the formation of 6-hmA and 6-fA, which can restore the original base (Figure 3) by releasing formaldehyde (Fu et al, 2013).…”
Section: Non-cytosine Methylation Of Dna: N6-methyladeninementioning
confidence: 99%
See 1 more Smart Citation
“…Methylation of adenine, i.e., 6-mA, in GATC context has been reported for the survival of several bacteria, as DNA adenine methyl transferase (DAMT, the writer) creates specific methylation marks (Figure 3) that are important for DNA replication, mismatch repair, segregation, and regulation of gene expression (Ratel et al, 2006). 6-mA is known to play an important regulatory role in RNAs, and recent studies suggest the presence of 6-mA in eukaryotic genomes (Kigar et al, 2017; Yao et al, 2017, 2018). Moreover, oxidation of the methyl group of 6-mA by AlkB family of dioxygenases (e.g., 6-mA demethylases) results in the formation of 6-hmA and 6-fA, which can restore the original base (Figure 3) by releasing formaldehyde (Fu et al, 2013).…”
Section: Non-cytosine Methylation Of Dna: N6-methyladeninementioning
confidence: 99%
“…Their finding indicates that cytosine and adenine (de)methylation occur in a coordinated, dynamic and sequence context-specific manner. Recently, Yao et al (2018) reported epigenetic regulation of a group of genes involved in neurodevelopment and neuronal functions in D. melanogaster . Accumulation of 6-mA due to deactivated DMAD coordinates with Polycomb proteins and contributes to transcriptional repression of the genes.…”
Section: Non-cytosine Methylation Of Dna: N6-methyladeninementioning
confidence: 99%
“…This effect can be overcome by ATP-dependent chromatin remodelers in vitro. We expect the biochemical impact of 6mA to be directly pertinent across a wide range of eukaryotic genomes, including vertebrates, C. elegans, Drosophila and fungi, where this 24 epigenetic modification has recently been documented Koziol et al, 2015;Liang et al, 2018;Liu et al, 2016;Mondo et al, 2017;Wu et al, 2016;Xiao et al, 2018;Yao et al, 2018;Zhang et al, 2015). Our experiments do not reveal exactly how 6mA disfavors nucleosome occupancy.…”
Section: Discussionmentioning
confidence: 67%
“…6mA exists at low levels in Arabidopsis thaliana (0.006%-0.138% 6mA / dA), rice (0.2%), C. elegans (0.01-0.4%), Drosophila (0.001-0.07%), Xenopus laevis (0.00009%), mouse ES cells (0.0006 -0.007%), human cells Koziol et al, 2015;Liang et al, 2018;Wu et al, 2016;Xiao et al, 2018;Zhang et al, 2015;Zhou et al, 2018) and the mouse brain (Yao et al, 2017), although it accumulates in abundance (0.1-0.2%) during vertebrate embryogenesis . Disruption of DMAD, a 6mA demethylase, in the Drosophila brain leads to the accumulation of 6mA and Polycomb-mediated silencing (Yao et al, 2018). The existence of 6mA in mammals remains a subject of debate.…”
Section: Introductionmentioning
confidence: 99%
“…N6-methyladenine (6mA) and 5-methylcytosine (5mC) are the two most prevalent and well-studied base methylations. 5mC usually plays a role in embryonic development [3], atherosclerosis [4], aging and diseases [5]; and 6mA is important in transcriptional regulation [6], cancer development [7] and neurodevelopment [8].…”
Section: Introductionmentioning
confidence: 99%